A Prevalence of Probable Migraine and Episodic Tension-Type Headache among Working Adults and their association with Headache-Related Quality of Life in Lahore, Pakistan. - Muhammad Salman; Fatima, Zanjeel; Mumtaz, Omer Mahmood; Anzish Waseem; Dania Asif; Zia Ur Rasool; Amama Zafar; Zoish Fatima (International Journal of Endorsing Health Science Research, 2026)
Background: Migraine and episodic tension-type headache (ETTH) are among the most common primary headache disorders worldwide and represent a major cause of disability, impaired productivity, and reduced quality of life among working-age populations. Despite their substantial public health burden, epidemiological evidence regarding headache-related disorders among working adults in Pakistan remains limited. This study aimed to estimate the prevalence of probable migraine and probable ETTH among working adults in Lahore, Pakistan, and to evaluate their association with headache-related quality of life across physical, social, and mental domains. Methodology: A descriptive cross-sectional study was conducted among 320 working adults using convenience sampling. Data were collected using the Headache Screening Questionnaire (HSQ) and the Comprehensive Headache-Related Quality of Life Questionnaire (CHQQ). Since HSQ is a screening instrument and not a diagnostic tool, all classifications were interpreted as probable headache-related conditions rather than clinically confirmed diagnoses. Statistical analysis was performed using the Mann–Whitney U test and Kruskal–Wallis H test. A p-value of <0.05 was considered statistically significant. Results: Among the participants, 35.9% demonstrated features suggestive of probable ETTH, while 16.3% demonstrated features suggestive of probable migraine. Approximately 32.8% of participants showed no headache-related features. Migraine-like symptom profiles were associated with significantly poorer overall headache-related quality of life compared with ETTH-related symptoms (p < 0.001). Females demonstrated significantly greater impairment in quality of life than males (p < 0.05). Domain-wise analysis further revealed significant differences in physical, social, and mental quality of life dimensions, particularly among participants with migraine-related symptoms. No consistent statistically significant associations were observed with age, marital status, sleep duration, or working hours. Conclusion: The findings demonstrate a considerable burden of headache-related symptoms among working adults, with probable migraine associated with greater functional and psychological impairment than probable ETTH.